Perlindungan Hukum Terhadap Perempuan Sebagai Korban Kejahatan Pornografi Balas Dendam (Revenge Porn) di Media Sosial - Ida Ayu Trisna Dewanti Dipayana; Ida Bagus Anggapurana Pidada (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
This research discusses the form of legal protection for women as victims of crime (revenge porn) on social media according to the TPKS Law and the obstacles in providing legal protection to women as victims of revenge porn crimes on social media. This research uses normative legal research. The data from this research is collected by literature study in the form of written regulations, theories from books and journals. The results of this study indicate that: first, the legal protection of victims of revenge porn in the TPKS Law, one of which is regulating the rights of victims such as handling, protection and recovery from cases of sexual violence. Second, obstacles in providing protection to women victims include the deep-rooted patriarchal culture and the distribution of intimate photos / videos considered as consensual. The conclusions of this study are: first, the enactment of Law No.12 of 2022 concerning Criminal Acts of Sexual Violence provides a positive signal in the prevention, handling and recovery of victims of sexual violence such as revenge porn.Second, the entrenched patriarchal culture is one of the obstacles in providing legal protection to women victims of revenge porn on social media.